Impacts of clinicopathological factors on efficacy of trastuzumab deruxtecan in patients with HER2-positive metastatic breast cancer. (February 2022) - Nakajima, Hiromichi; Harano, Kenichi; Nakai, Tokiko; Kusuhara, Shota; Nakao, Takehiro; Funasaka, Chikako; Kondoh, Chihiro; Matsubara, Nobuaki; Naito, Yoichi; Hosono, Ako; Mitsunaga, Shuichi; Ishii, Genichiro; et al.
Abstract: Background: The previous second-line treatment for HER2-positive metastatic breast cancer were ado-trastuzumab emtansine (T-DM1); however, its activity is decreased in tumors with heterogenous, reduced, or loss of HER2 expression. Trastuzumab deruxtecan (T-DXd) has recently been developed as a novel antibody-drug conjugate to overcome resistance to T-DM1. However, clinical evidence on its ability to overcome this resistance is limited. Materials and methods: We retrospectively analyzed data for patients with HER2-positive metastatic breast cancer who received T-DXd at our institution from April 2020 to March 2021. We evaluated the associations between clinicopathological and molecular biomarkers and the efficacy of T-DXd. Results: Twenty-two patients were enrolled in this study. The median progression-free survival (PFS) was 9.7 months (95% confidence interval [CI], 7.0–not reached [NR]), and the objective response rate (ORR) was 61.9%. The ORR and PFS were comparable between patients with HER2 immunohistochemistry scores of 3+ and 2+/1+ at initial diagnosis (ORR: 50.0% vs. 72.7%, p  = 0.39; median PFS, 9.7 months [95%CI, 2.6–NR] vs. 8.3 months [95%CI, 7.1–NR]; hazard ratio, 1.86 [95%CI, 0.53–6.57], p  = 0.34). Two patients with heterogenous HER2 expression had a partial response or long stable disease (≥6 months). Three of four patients with re-biopsy samples after anti-HER2 targeted therapy and with latest HER2 immunohistochemistry scores of 1+ experienced partial responses (75.0%) to T-DXd, but none had responded to prior T-DM1. Conclusions: T-DXd demonstrated favorable activity in clinical practice. Moreover, T-DXd showed meaningful benefit in patients with heterogeneity, reduction, or loss of HER2 expression. Highlights: T-DXd showed favorable clinical activity against HER2-positive metastatic breast cancer. T-DXd showed benefit in patients with heterogeneity, reduction, or loss of HER2 expression. Patients with liver metastasis tended to have worse outcomes.